STAT3-Dependent Gene TRIM5γ Interacts With HBx Through a Zinc Binding Site on the BBox Domain - Song, Hongxiao; Xu, Fengchao; Pang, Xiaoli; Xiao, Qingfei; Wei, Qi; Lei, Bingxin; Li, Xiaolu; Fan, Xixi; Tan, Guangyun (Frontiers in Microbiology, 2021)
Owing to its broad-spectrum antivirus activities, interferon (IFN) is an important alternative agent for use in the treatment of hepatitis B virus (HBV)-infected patients; however, the mechanism involved in the inhibition of HBV infection and replication by IFN remains unclear. We previously reported that the induction of TRIM5γ is important in the IFN treatment of HBV patients as it promotes the degradation of the HBx protein, while the manner in which TRIM5γ is induced by IFN and how TRIM5γ interacts with HBx remain unestablished until date. Our present findings indicated that STAT3, and not STAT1, is responsible for the induction of TRIM5γ upon IFN stimulation and that the zinc binding site His123 on the BBOX domain is a decisive site in the interaction between TRIM5γ BBOX and HBx. In addition, based on the BBOX domain, we detected a 7-amino acid peptide with the potential of promoting HBx degradation and inhibiting HBV replication. On the other hand, we noted that the TRIM5γ expression is inhibited by HBV in chronically HBV infected patients. Thus, our study identified the crucial role of STAT3 in the induction of TRIM5γ, as well as proposed a 7-amino acid, small peptide as a potential candidate for the development of therapeutic agents targeting HBx.